Competition between ferromagnetism and frustrated antiferromagnetism in quasi 2D Ce2.15(Pd1−xAgx)1.95In0.9 alloys. (16th September 2016) - Sereni, J G; Giovannini, M; Gómez Berisso, M; Gastaldo, F
Abstract: Low temperature thermal and magnetic measurements performed on ferro-magneticl (FM) alloys of composition Ce2.15 (Pd1− x Ag x )1.95 In0.9 are presented. Pd substitution by Ag depresses T C ( x ) from 4.1 K down to 1.1 K for x = 0.5, which is related to the increase of band electrons, with a critical concentration extrapolated to x c r ≈ 0.6 . The T C ( x ) decrease is accompanied by a weakening of the magnetization of the FM phase. At high temperature ( T > 30 K) the inverse magnetic susceptibility reveals the presence of robust magnetic moments ( 2.56 ⩾ μ e f f ⩾ 2.4 μ B ), whereas the low value of the Curie–Weiss temperature θ P ≈ − 10 K excludes any relevant effect from Kondo screening. The specific heat jump at T C ( x ) decreases accordingly, while an anomaly emerges at a fixed temperature T ∗ ≈ 1 K. This unexpected anomaly does not show any associated sign of magnetism checked by AC-susceptibility measurements. Since the total magnetic entropy (evaluated around T = T C ( x = 0 ) ) practically does not change with Ag concentration, the transference of degrees of freedom from the FM component to the non-magnetic T * anomaly is deduced. The origin of this anomaly is attributed to an arising magnetic frustration of the ground state and the consequent entropy bottleneck produced by the divergent increasing of density of excitations at low temperature.